OPTIMALISASI SAMPAH PLASTIK PASCA TERJADINYA LONJAKAN WISATAWAN PERDESAAN BROMONILAN KABUPATEN SLEMAN YOGYAKARTA - Sudiro, Syawal; Nugroho, Agung Yuliyanto (Kepariwisataan: Jurnal Ilmiah, 2021)
Bromonilan Tourism Village or DEWA BROMO is a rural tourism object of Sleman Regency based on local communities or Community-Based Tourism which was established based on a Pokdarwis Decree dated January 7, 2019. This tourist village located on the banks of Kali Kuning offers a concept of rural tourism destinations. The surge in tourists in the weekends has an impact on the accumulation of garbage in the Bromonilan environment. The research method used in this research is to study data through observation, in-depth interviews with the manager and study documentation. Research shows that there has been no significant optimization of plastic waste since this tourist village was established in January 2019 to January 2021 so that the remaining plastic waste from visiting tourists is neglected so it is necessary to optimize plastic waste into paving blocks. Keywords: Rural Tourism, Plastic Waste, Paving Blocks, Lord Bromo